Empowering the Youths through the Skilled Youth Program III as Citi Indonesia's Corporate Social Responsibility Activity - Insan Faqihantara; Worry Mambusy Manoby (Institute for Research and Community Services, 2020)
Decent Work and Economic Growth represent one of the goals of Sustainable Development Goals. The Government of Indonesia through the National Secretariat for Sustainable Development Goals has continued to launch national actions by building multi-stakeholder partnerships to encourage the achievement of these goals. Citi Indonesia, together with Indonesia Business Links, initiated a youth development and empowerment program in the area of Bekasi City, Bekasi Regency, Karawang Regency, Purwakarta Regency, and Bandung Regency. The collaboration was a Citi Indonesia Corporate Social Responsibility activity focusing on capacity building, opening job opportunities, encouraging entrepreneurship, and creating a conducive environment. Increased competence in human resources is needed especially in the current 4.0 industrial revolution era. The shift of human labour into machines with automation and the digital economy requires workers who have the intermediate ability. This happens because much low-skilled human labour has been replaced by machines. The program aimed to prepare young people to be ready to work and ready for entrepreneurship. This program was designed as a series of activities with implementation methods in the form of focus group discussions, outreach, in-class training, seminars, counselling, and field practice. The results showed an increase in the knowledge and skills of the training participants so that it is hoped they will have a greater opportunity to be employed or to become entrepreneurs.